3D-Printed specimens as a valuable tool in anatomy education: A pilot study - Garas, M.; Vaccarezza, Mauro; Newland, G.; McVay-Doornbusch, K.; Hasani, J. (2018)
Three-dimensional (3D) printing is a modern technique of creating 3D-printed models that allows reproduction of human structures from MRI and CT scans via fusion of multiple layers of resin materials. To assess feasibility of this innovative resource as anatomy educational tool, we conducted a preliminary study on Curtin University undergraduate students to investigate the use of 3D models for anatomy learning as a main goal, to assess the effectiveness of different specimen types during the sessions and personally preferred anatomy learning tools among students as secondary aim. The study consisted of a pre-test, exposure to test (anatomical test) and post-test survey. During pre-test, all participants (both without prior experience and experienced groups) were given a brief introduction on laboratory safety and study procedure thus participants were exposed to 3D, wet and plastinated specimens of the heart, shoulder and thigh to identify the pinned structures (anatomical test). Then, participants were provided a post-test survey containing five questions. In total, 23 participants completed the anatomical test and post-test survey. A larger number of participants (85%) achieved right answers for 3D models compared to wet and plastinated materials, 74% of population selected 3D models as the most usable tool for identification of pinned structures and 45% chose 3D models as their preferred method of anatomy learning. This preliminary small-size study affirms the feasibility of 3D-printed models as a valuable asset in anatomy learning and shows their capability to be used adjacent to cadaveric materials and other widely used tools in anatomy education.